IMPROVING THE QUALITY OF POTATO MINI TUBERS BY SUSTAINABLE CULTIVATION - A. D. Salman; W. A. Hussein; Sh. A. Zaili; A. O. Mhawesh (مجلة الأنبار للعلوم الزراعية)
This study aimed at improving the quality of potato tubers using vermicompost and plant extracts. It employed the RCBD design with three replicates within the factorial experiment (3*5). The factors included vermicompost at two levels of 0.5 and 1% designated V1 and V2, respectively, and treatment without vermicompost (V0). The second treatment involved foliar application of Cyperus Rotundus root extracts at 5 and 10 g L-1 designated T1 and T2, respectively, and Silybum marianum leaf extract at 5 and 10 g L-1 (T3 and T4 respectively), and spraying the control treatment with water (T0). The results showed significant improvements in treatment involving vermicompost and spraying with Silybum marianum leaf extract (V2T3) in terms of dry matter percentage of the tubers, their specific density, and percentages of starch, nitrogen, protein, carbohydrates and phenols at 28.55, 1.119, 21.44, 1.71, 10.68, 11.43% and 3.13 mg 100 g, respectively. This did not differ significantly in the percentage of dry matter and specific density of the tubers, their percentage of starch from the V0T3 treatment, the percentage of nitrogen and protein in the tubers for treatments V2T4, V1T3, V2T2, and V1T4, in carbohydrates for treatment V1T4, and in total phenols for treatment V2T2, V1T3, and V0T3 compared to the measured plants, which recorded 21.71, 1.087, 15.34, 1.35, 8.43, 5.56%, and 1.14 mg 100 g, respectively. Therefore, the application of 1% vermicompost and spraying of 5 g.L-1 Silybum marianum leaf extract is recommended for improving the quality of potato tubers and for sustainable cultivation. This will also promote recycling and preserve the environment.